Effects of tributyltin chloride on different life stages of brine shrimp, Artemia salina (Linnaeus, 1758) - Shaala, Najla Mohamed Abou (2017)
Organotin is one of the most effective antifouling biocides ever invented to reduce the threats pose by fouling organisms. A previous risk assessment of this biocide has been inadequate, so that its possible effects on aquatic ecosystems are a matter of great concern.This study explored the responses of common marine water AnostracaArtemia salina to lethal concentration of a type of organotin, tributyltin chloride (TBTCl) under different concentration, similar environmental conditions and at various stages of the lifestyle. Endpoints of this study encompassed hatching inhibition of cyst stage, mortality percentage in different stages of the life cycle A. salina, morphological changes in different stages, histological study about the pathological lesion changes in epithelial layer in gut A. salina, and effects TBTCl on reproductive organs, ovaries and testes with used Caspase-3 and HSP70 antibody inthe adult stage to enable a comprehensive analysis of the effects on the organism. Samples for this study were obtained from Aqua fauna Bio Marine (Hawthorne, California, U.S.A). A. salina cysts hatched under the recommended physicochemical parameters. In the first experiment, the cysts were exposed to different the concentrations of TBTCl (5, 10, 15, 20, 25, 50, 75, 100, 150, 200 ng.L-1) for 24 hours and observed hatchability performance, and influenced the percent survival to determine the median effective concentration 50% (EC50).Then, cysts hatchability performance of different stages of A. salina under different concentration of TBTCl in the artificial sea water was studied. Median lethal concentration (LC50) of different life stages of A. salina under different concentration of TBTCl (1, 25, 50, 100, 150, 200, 250, 300, 350, 400, 450, 500 ng.L-1), were determined via acute toxicity test for 24 hours. LC50 bioassay method was carried out to study acute toxicity of TBTCl on different stages of A. salina. After that, we studied the morphological changes and histopathological lesions in the epithelial layer at different stages life cycleof A. salina. The samples for histological evaluation were placed in Boun'sfixative and continued with normal steps in histology method with minor modification. The prepared samples were stained with hematoxylin and eosin method, examined under a light microscope and recorded some photomicrographs for documentations. Immunohistochemistry (IHC) for the first time used to study reproductive organs males and females Artemia sp after exposed to TBTCl. In brief IHC used to see effects of TBTCl on gonad tissue, where IHC using specific apoptosis markers where they followed these steps start with primary antibody on the gonad tissue and the primary antibody it will be attachment with the antigen in tissue, and then add the secondary antibody which will be linked with primary antibody. After that, add AB enzyme complex (ABC) (Avidin/Biotinylated). Finally, add enzyme substrate (DAB- chomogen) and the results as positive immunostaining were observed as brownish deposits, indicating the location of the Caspase-3 or HSP70 antigen-antibody reaction.Results showed TBTCl has the ability to inhibitor hatching process of A. salina cysts when increasing the concentration of TBTCl and affects morphological development (total length and body width) of active nauplii. LC50 values of nauplii, juvenile adult male and adult female are 469.08, 226.69, 146.99 and 94.72 respectively. LC50results showing the most sensitive stage to TBTCl is an adult female stage compared to other stages. The morphological results showed higher regression values, thus demonstrate a strong inverse relationship between morphological measurements for total length and body width by increasing TBTCl in different stages of A. salina. This study revealed for the first time study effects TBTCl on A. salina cell structure and revealed the pathological changes. Based on the findings the effects of toxicity TBTCl on A. salina tissues were associated with pathological lesions, which cause the mortality following exposure. Besides that, IHC revealed the apoptosis marker and immune system stress of the A. salina reproductive gonads in adults. In conclusion,these results confirmed that the females are more sensitive to TBTCl toxic compared to males. All results of present study strongly agree that TBTCl can cause various biological effects to target and non-targeted organisms, especially in the TBT contaminated areas with intensive shipping and industrial activities. Furthermore, this study showed that Artemia sp. is a good model organism to be used as a bioindicator for marine pollution studies. Since there are no detail studies on effects of TBTCl on cellular structures of model organisms, including Artemia sp., this study also reconfirms the suitability of the A. salina for bioassay in assessing marine aquatic toxicity profile of any toxicant with simple and reproducible results.